2012
DOI: 10.1097/sla.0b013e31822518e6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mesh During Ventral Hernia Repair in Clean-Contaminated and Contaminated Cases

Abstract: There is a significant increase in risk of postoperative occurrences following VHRs using mesh in clean-contaminated and contaminated cases relative to clean cases. We recommend avoiding the use of mesh in any level of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(100 citation statements)
references
References 10 publications
2
97
0
1
Order By: Relevance
“…In a large study by Choi et al from the National Surgical Quality Improvement Program (NSQIP) registry in the United States, including 33,832 patients demonstrated a higher risk for SSO in clean-contaminated and contaminated compared to clean cases using a mesh. There was also an increased risk of SSI in clean-contaminated cases after the use of mesh versus no mesh as anticipated [18].…”
Section: Recommendationsmentioning
confidence: 80%
“…In a large study by Choi et al from the National Surgical Quality Improvement Program (NSQIP) registry in the United States, including 33,832 patients demonstrated a higher risk for SSO in clean-contaminated and contaminated compared to clean cases using a mesh. There was also an increased risk of SSI in clean-contaminated cases after the use of mesh versus no mesh as anticipated [18].…”
Section: Recommendationsmentioning
confidence: 80%
“…Over the last 20 years, tension-free repair of massive ventral hernia with mesh, especially by laparoscopy, becomes gradually popular with much better outcomes, such as less postoperative abdominal pain and a decreased recurrence rate close to 15% [2,3,[5][6][7][8][9][10]. However, most research on massive ventral hernia repair is about modification of the existing approaches or surgical methods, including abdominal wall reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In a retrospective chart review of outcomes in 35 high-risk ventral herniorrhaphy patients, Janfaza et al found that rates of postoperative infection and hernia recurrence at 1 year were lower in patients who received a neonatal bovine mesh implant (SurgiMend, TEI Biosciences, Boston, Massachusetts) (17% and 5%, respectively) compared with patients who received a humanderived mesh (Flex HD, Ethicon Inc, Somerville, New Jersey) (50% and 33%, respectively). 26 In a large prospective chart analysis of .33,000 patients from the US National Surgical Quality Improvement Program (NSQIP) who underwent ventral hernia repair, Choi et al found that patients with some level of operative field contamination were three-to fivefold more likely to experience postoperative complications than those with clean surgical fields.…”
Section: Discussionmentioning
confidence: 99%